Let's just ask them. Perspectives on urban dwelling and air quality: A cross-sectional survey of 3,222 children, young people and parents. - Rachel Juel; Sarah Sharpe; Roberto Picetti; James Milner; Ana Bonell; Shunmay Yeung; Paul Wilkinson; Alan D Dangour; Robert C Hughes (Public Library of Science (PLoS), 2023)
This research aimed to capture and synthesise the views of children, young people, parents and expectant parents (CYPP) about the cities where they live, with a specific focus on air pollution (AP), in order to support the generation of evidence-informed policy that reflects CYPP's perspectives, ultimately contributing to the development of child-centered, healthier, sustainable cities. The Children, Cities and Climate (CCC) project used targeted social media adverts to recruit CYPP to complete an online survey with a combination of open and closed questions in order to collect perceptions about air quality in their home cities, the main sources of AP, and how they would improve their cities. The survey was completed by 3,222 CYPP in 59 of the most polluted cities in 14 countries. Nearly two in five (39%) CYPP cited AP as one of the worst things about their city, with motor transport perceived as the main contributor. CYPP reported differing views on whether their cities were becoming better (43%) or worse (34%) places to live (33% reported it was 'staying the same'). Numerous specific ideas to improve cities and urban air quality emerged, alongside an emphasis on also addressing structural barriers to change. A clear set of principles that should guide how city leaders act was also described, including the need to engage with young people meaningfully. CYPPs articulated good and bad experiences of urban living and perceived AP and traffic as pressing concerns. They provided a clear set of suggestions for improving their cities. Further efforts to engage young people on these issues are warranted.